ANALYSIS OF TECHNOLOGIES FOR OBTAINING ALTERNATIVE ENERGY SOURCES AND COMPARISON OF THE MAIN CHARACTERISTICS OF THE EFFICIENCY OF PHOTOVOLTAIC CONVERTERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article provides a comparative analysis of technologies for obtaining alternative energy sources and compares the main characteristics of the efficiency of photovoltaic converters. In order to study the parameters of photoelectric converters, the materials used in their manufacture are considered, and their current-voltage characteristics are compared. The operating temperature range, generated current and overall dimensions of photoelectric converters are also analyzed.